Effects of 11-week volume-equated hypertrophic strength training performed at workplace in one or two sessions on isometric strength and muscle CSA in untrained men - Hietanen, Pauliina (2020)
Background. As the recommended amount of weekly resistance training tends to fall short, introducing low-threshold options for resistance training incorporated within working day could turn out beneficial. Consensus exists about the benefits of short bouts of physical activity accumulated within a day, but limited research exists about the applicability of shorter daily resistance training sessions applied within a day in relation to single volume-matched training session performed once a day. Aim. The purpose of this study was to determine, whether moderate-load hypertrophic strength training performed at the workplace with unconditional training equipment in one or two sessions of equated volume, would increase isometric maximal voluntary contraction (MVC) strength, muscle cross-sectional area (CSA) and total muscle mass. These parameters were examined for within and between group differences regarding their absolute and relative values. Methods. Previously untrained male subjects were divided into two groups: One-Session Group (n = 7, age 35.2 ± 4.4 years, BMI 24.5 ± 2.8, leg press MVC/bodyweight 3.29 ± 0.47, bench press MVC/bodyweight 0.84 ± 0.17) and Two-Session Group (n = 7, 32.4 ± 5.0, BMI 25.8 ± 3.2, leg press MVC/bodyweight 3.21 ± 0.56 , bench press MVC/bodyweight 0.85 ± 0.19). After the 2-week control period, both groups performed moderate-intensity hypertrophic strength training at workplace for 11 weeks training on two days per week. The One-Session Group trained once per day performing two sets on 6 exercises, whereas the Two-Session Group trained twice per day performing one set on the same 6 exercises per training session. The intensity and total volume load (repetitions × sets × load) were matched between groups. Ultrasound measurement on vastus lateralis (VL) and triceps brachii (TB) CSA, InBody test for body composition, countermovement jump (CMJ) and isometric leg press and bench press MVC were measured on weeks -2, 0, 3, 7, 11. Results. After 11 weeks of training, no statistically significant differences were observed between groups on any measured performance, muscle CSA or body composition variable. Both groups improved their leg press MVC (One-Session Group: 18.6 ± 5.1 %, p < 0.05; Two-Session Group: 14.9 ± 11.5 %) and bench press MVC (One-Session Group: 17.4 ± 7.7 %, p < 0.05; Two-Session Group: 19.3 ± 8.3 %). Both groups increased their VL CSA (One-Session Group: 7.6 ± 5.7 %, Two-Session Group: 7.5 ± 10.7 %) and TB CSA (One-Session Group: 11.2 ± 3.7 %, p < 0.01; Two-Session Group: 8.9 ± 5.3 %). For combined data, there were statistically significant increases both for VL (p < 0.01) and TB (p < 0.001) CSA from Pre to Post measurements. Both groups increased their muscle mass (One-Session Group: 2.5 ± 2.1 %, Two-Session Group: 3.5 ± 2.5 %). When combined, there was a statistically significant increase in muscle mass from Pre to Post measurements (p < 0.001). Conclusions. Both approaches were equally effective in increasing strength, muscle CSA and muscle mass. Leg press MVC and bench press MVC increased relatively similarly during the intervention in both groups. Hypertrophic strength training performed at workplace can be an effective way to increase muscle strength, muscle size and muscle mass regardless a single 1-hour or two 0.5-hour sessions are completed during a day.